Evaluating hydrological dynamics and water quality in agricultural landscapes in Ghana’s Forest Transition Belt: a citizen science approach - Adusei-Gyamfi, J.; Gyebi, A. S. A.; Amponsah, Andoh Kwaku; Atampugre, Gerald; Tilahun, Seifu A.; Cofie, Olufunke O. (International Water Management Institute (IWMI). CGIAR Initiative on West and Central African Food Systems Transformation, 2023)
Food system transformation is intrinsically tied to effective land and water resource management, especially in the regions facing competition among various land uses. The AhafoAno Southwest District in Ghana exemplifies this complexity, with agriculture, mining, and agroforestry practices competing against one another for arable land, impacting the local food system and contributing to water resource degradation. This study investigates the quantity and quality of water in the Mankran watershed, employing a participatory approach through citizen science to address the increasing challenges within the Ahafo-Ano Southwest district. To conduct this investigation, a team of seven citizen scientists, including four women, was carefully selected from the local community, and equipped with the training to monitor water resources effectively. The Mankran watershed, within the Ahafo-Ano District, was chosen for its strategic representation of different land-uses that affect water resources. The study focused on three distinct riparian communities: Mmrobem, representing the upstream with agroforestry as the predominant land use; Barniekrom, representing the midstream with agricultural activities prevailing; and Kunsu, representing the downstream with mining activities as the predominant land use. Installation of staff gauges at midstream and downstream locations facilitated streamflow measurements, while manual rain gauges were deployed in each community for comprehensive rainfall measurements. Additionally, groundwater monitoring involved the selection of two wells in Mmrobem, three in Barniekrom, and two in Kunsu. Basic hydrological variables such as daily rainfall, streamflow rate, and groundwater level, along with water quality parameters (pH, turbidity, dissolved oxygen, nitrate, phosphate, chloride, and heavy metals), were diligently measured by the citizen scientists from June to October 2023. Monthly water samples were sent to a laboratory for further technical analysis, including the determination of heavy metals. The data revealed rainfall variations impacting six-month streamflow, notably in midstream and downstream areas. Downstream, influenced by mining, experienced twice as more streamflow rate, indicating potential mining runoff. Water quality assessments showed pH, turbidity, dissolved oxygen, nitrate, and phosphate variations, influenced by community land use. Nitrate concentrations peaked in the rivers in June, while wells in agricultural lands showed consistently high concentrations, likely due to leaching. Phosphate concentrations increased as the rainy period progressed in streams mirroring well concentrations, signifying subsurface flow dominance. Mercury concentrations were low in surface water but four times higher in groundwater. Despite the challenges posed by mining activities, the citizen scientists demonstrated their capacity to provide reliable semi-technical measurements comparable to standard laboratory analyses. This not only confirmed the efficacy of citizen science in environmental monitoring but also empowered these individuals to become environmental stewards within their communities. The study further emphasized the dominance of subsurface flow in the landscape, with implications for potential transport mechanisms for water quality in the landscape. The water quality index indicated poor conditions across all study sites, emphasizing the urgent need for a comprehensive integrated landscape management plan. This plan must consider the role of subsurface flow to safeguard environmental resources, enhance water quality, and protect human health. The commitment of all stakeholders is also paramount to successfully implementing such a plan and ensuring the sustainable development of the Ahafo-Ano Southwest district.